Predictive Score for Carbapenem-Resistant Gram-Negative Bacilli Sepsis: Single-Center Prospective Cohort Study - Marisa Zenaide Ribeiro Gomes; Douglas Quintanilha Braga; Debora Otero Britto Passos Pinheiro; Renata Cristina Amorim Silveira Verduc; Letícia Vellozo dos Reis; Elisangela Martins de Lima; Newton Dias Lourenço; Patrícia Aquen Cid; Debora Souza Beck; Luiz Henrique Zanata Pinheiro; João Pedro Silva Tonhá; Luiza Silva de Sousa; et al. (MDPI AG, 2022)
A clinical-epidemiological score to predict CR-GNB sepsis to guide empirical antimicrobial therapy (EAT), using local data, persists as an unmet need. On the basis of a case-case-control design in a prospective cohort study, the predictive factors for CR-GNB sepsis were previously determined as prior infection, use of mechanical ventilation and carbapenem, and length of hospital stay. In this study, each factor was scored according to the logistic regression coefficients, and the ROC curve analysis determined its accuracy in predicting CR-GNB sepsis in the entire cohort. Among the total of 629 admissions followed by 7797 patient-days, 329 single or recurrent episodes of SIRS/sepsis were enrolled, from August 2015 to March 2017. At least one species of CR-GNB was identified as the etiology in 108 (33%) episodes, and 221 were classified as the control group. The cutoff point of ≥3 (maximum of 4) had the best sensitivity/specificity, while ≤1 showed excellent sensitivity to exclude CR-GNB sepsis. The area under the curve was 0.80 (95% CI: 0.76-0.85) and the number needed to treat was 2.0. The score may improve CR-GNB coverage and spare polymyxins with 22% (95% CI: 17-28%) adequacy rate change. The score has a good ability to predict CR-GNB sepsis and to guide EAT in the future.